PENGEMBANGAN MODEL PERMAINAN DI SD/MI - Pika, Pika (Adisam Publisher, 2026)
Learning in elementary school requires strategies that are in accordance with the developmental characteristics of children who are active and enjoy playing activities. One innovation that can be applied is the development of game-based models in learning. This article aims to analyze the concepts, development procedures, and the effectiveness of game-based models in improving the activities and learning outcomes of elementary school students. The method used is a literature study by reviewing various theoretical sources and relevant research results. The findings indicate that game-based models can increase motivation, active participation, social skills, as well as students' conceptual understanding. The implications of this study emphasize the importance of teacher creativity in designing educational games that align with learning objectives and the characteristics of elementary school students.